Increased ability to arrange two tier multiple choice questions - Pantiwati, Yuni; Mahmudati, Nurul (Journal of Community Service and Empowerment, 2021)
SMP Muhammadiyah 2 Malang City is a school which is located on Jl Letjen Sutoyo No 68 Malang City. This school has great potential and has the opportunity to carry out two tier multiple choice question-making service activities because the school is the school's top priority (partner). The problem faced is that teachers have never compiled Two Tier Multiple Choice questions, especially science teachers. The science teacher said that he was always prepared questions for student evaluation instruments, either formative, sub-summative or summative, but the questions that were arranged were still conventional. The teacher said that he was not yet skilled in compiling HOTS questions, let alone the type of Two Tier Multiple Choice that he had never known. Activities to be carried out are socialization of teacher training programs, pre-test teacher assistance. Teachers have increased their abilities regarding the preparation of Two Tier Multiple Choice questions. The teacher-made question products have 30 sets or 60 items, and have been tested with the results of the questions that qualify as good questions